Pengaruh Beban Kerja dan Burnout Terhadap Kinerja Organisasi KPU di Provinsi Lampung - Kristina Uli Syahrani Br Sitorus; Khairudin Khairudin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of workload and burnout on organizational performance at the General Election Commission (KPU) of Lampung Province. The background of this research is based on the high work demands and organizational pressure that potentially affect employees’ psychological conditions and overall organizational performance. This research employed a quantitative approach with an associative method. Data were collected through questionnaires distributed to 29 employees of the KPU of Lampung Province selected using purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results show that workload has a negative but not significant effect on organizational performance. Meanwhile, burnout has a negative and significant effect on organizational performance. Simultaneously, workload and burnout have a negative and significant effect on organizational performance. These findings indicate that work-related exhaustion plays a crucial role in reducing organizational effectiveness and productivity. Therefore, integrated management of workload and burnout prevention is essential to improve organizational performance. This study is expected to contribute to the development of human resource management practices in the public sector.